Grape seed proteins: a new fining agent for astringency reduction in red wine. (13th May 2013) - Vincenzi, S.; Dinnella, C.; Recchia, A.; Monteleone, E.; Gazzola, D.; Pasini, G.; Curioni, A.
Abstract Background and Aims Protein‐fining agents from animal and plant sources are used to clarify and stabilise wines and lower their astringency. Health concerns have been raised because most of the proteins used for wine fining are derived from allergenic sources. To overcome this problem, this study proposed the use of a grape seed protein extract as a new fining agent for wine. Methods and Results The procedure is described for extract preparation from grape seed flour, the by‐product of the grape oil seed industry. Four extracts of grape seed protein were prepared using glycine and sodium carbonate buffers at two concentrations (0.05 and 0.2 M, pH 10.5). The capacity of the extracts for removing potentially astringent phenols from tannin solutions and from red wines was assessed by determining the Astringency Mucin Index. The perceived astringency intensity in tannin solutions and in two red wines treated with the extracts was evaluated by sensory tests. Conclusions The Astringency Mucin Index and astringency intensity of treated samples were significantly lowered compared to that of untreated samples. Significance of the Study Grape seed extracts appear a promising tool for wine fining as a substitute for exogenous proteins.